Associations between dietary nutrient intake and sleep disorders in cancer survivors base on NHANES 2005 to 2018 - Qian Wu; XueFeng Yang; Zhiyu Wang; Kai Zhou; Hang Yang; Lixia Zhou; Xiaoxia Gou (Scientific Reports)
Abstract Sleep disorders significantly impact the quality of life for many individuals, which remain largely unrecognized. It is widely believed that dietary nutrient intake plays a crucial role in promoting healthy sleep patterns. However, there is lack of research focusing on cancer survivors. This study utilized the National Health and Nutrition Examination Survey (NHANES) database to investigate the correlation between dietary nutrient intake and sleep disorders in cancer survivors. Analyzing data from 2882 cancer survivors in NHANES spanning from 2005 to 2018. Dietary nutrient intake was evaluated through two 24-h dietary recalls. Weighted multivariable logistic regression model was employed to further applied to explore the association between dietary fiber intake and sleep disorders while controlling for relevant confounding factors. Additionally, the nonlinear and dose–response relationships were explored using restricted cubic spline (RCS) regression along with smooth curve fitting and threshold effect analysis. Stratified analysis and interaction analysis were conducted to assess the consistency of the results. Univariable and multivariable analysis demonstrated that dietary fiber intake showed negative correlation with sleep disorders (P < 0.05). Treating dietary fiber intake as continuous variable. After accounting for all covariates, the study reaffirmed the protective role of dietary fiber (odds ratio [OR]: 0.99, 95% confidence interval [CI]: 0.98–0.99, P = 0.044). Analysis of dietary fiber intake in quartiles further supported this trend (P < 0.001). Interestingly, further investigations indicated that dietary fiber intake was not associated with sleep apnea, insomnia, restless legs syndrome, or other types of sleep disorders (P > 0.05). Notably, no statistically significant interactions were observed in all subgroup analyses except poverty income ratio (PIR) (P for interaction < 0.05), indicating that the protective effect of dietary fiber on sleep disorders was more pronounced in individuals with PIR ≥ 2.5. Our results suggest that adequate dietary fiber intake may be beneficial dietary strategy to reduce sleep disorders in cancer survivors.